Bigels for controlled gastric release of ascorbic acid: Impact on rheology, texture, thermal stability and antioxidant activity - Admajith M. Kaimal; Rekha S. Singhal (Food Hydrocolloids for Health, 2023)
Ascorbic acid (AA) is a vital nutrient to maintain critical physiological functions but is very sensitive to processing and storage. This can be overcome by using gel-based systems for controlled release of AA. This study compares various gel-based formulations such as hydrogel, emulsion gel, bigel (25 %, 50 %, and 75 % oleogel), and emulsions for thermal stability and delivery of AA, rheological and textural profile, encapsulation efficiency (>97 %), in vitro gastrointestinal release profile, and the corresponding antioxidant profile. An increase in the oleogel content increased the hardness (125 – 216 g) and viscoelastic properties (G′ and G′′) but decreased (76.16 – 25.86 %) the swelling ratio of the bigel. A spontaneous release of AA was witnessed during gastric digestion from emulsion gels (95 %), hydrogels (98 %) and emulsions, whereas a gradual and controlled gastric release of AA could be achieved by bigels. However, a sudden decrease in AA (70 – 80 % reduction) and a spike in dehydroascorbic acid (DHA, oxidized AA) could be observed during intestinal digestion. The bioaccessibility was highest for emulsion gel and bigel (87 %) and lowest for emulsions (70 %). Bigels with higher oleogel content also showed better thermal stability but their physical stability was compromised at higher temperature. The DPPH and ABTS activity was proportional to AA, while FRAP was impacted by both DHA and AA. Thus bigels could be utilised for controlled gastric release of AA with better thermal stability.